Compartive Understanding Of Nikah Mut’ah & Misyarand Their Correlation With Human Trafficking Laws - Bhati, Bhaskar (Trinity Law Review, 2022)
The core of this work focuses on Nikah Mut’ah practice among Shia Muslims and its counterpart  among Sunni Muslims. i.e., Nikah Misyar and their misuse in the contemporary world to exploit  women for trafficking, prostitution and other associated criminal activities while maintaining the  facade of a perfectly legal process.The practice isn’t exclusive to any particular nation or continent but is more prevalent among  nations based on orthodox Islamic values as against the Universal Declaration of Human Rights  since the Shariah doesn’t exactly prohibit slavery.When it comes to organised crime syndicates working on a global level, trafficking in drugs,  weapons and humans present the most number of cases registered worldwide, respectively in that  order. It’s noteworthy that these activities often culminate into self-sustaining cartels that tend to  enter into symbiotic relationships where associates profit off of each other.
Keywords: Nikah Mut’ah; Misyarand; trafficking; prostitution